Los procesos cognitivos básicos de atención, memoria y la comprensión lectora en estudiantes de primer ciclo de Contabilidad y Auditoría paralelo B de la UNL, 2024. - Vicente Rojas, Nicole Cristina (2024)
The purpose of this Curricular Integration Research was to analyze the relation between the levels of the basic cognitive processes of attention, memory and reading comprehension of first-cycle students of the Accounting and Auditing, parallel B at the Juridical, Social and Administrative Faculty of the Universidad Nacional de Loja, 2024. The research follows a descriptive, correlational and transversal quantitative approach with a non-experimental design. The Test d2, which evaluates attention, RIAS memory subsystem and the ICLAU, were applied to evaluate the reading comprehension with a sample of 27 students. The statistic program SPSS was used to create a general statistical analysis of frequencies, global and comparative between variables. The results showed that the evaluated students maintain a low- level attention and a high-level memory; and, regarding reading comprehension, they were within the medium level. It was concluded that there is no relation between the cognitive process of attention and the reading comprehension, according to the statistic value of Kendall’s correlation coefficient, which is -.009. These results lead to reject the alternative hypothesis and accepting the null hypothesis. On the other hand, Kendall’s correlation coefficient value of 0.052 demonstrated that there is a substantial positive correlation between the cognitive process of memory and reading comprehension. Therefore, the alternative hypothesis is accepted, and the null hypothesis is rejected.